2022
DOI: 10.1186/s13148-022-01260-4
|View full text |Cite
|
Sign up to set email alerts
|

Data mining of bulk and single-cell RNA sequencing introduces OBI1-AS1 as an astrocyte marker with possible role in glioma recurrence and progression

Abstract: Long non-coding RNAs (LncRNAs) are widely known for their various functions in cancer from tumor initiation to tumor progression and metastasis. Gliomas are the most prevalent primary forms of brain tumor, classified into grades I to IV according to their malignant histological features with grade IV, also known as glioblastoma multiforme (GBM), displaying the highest level of malignancy. Thus, the search for differentially expressed LncRNAs in GBM versus low-grade glioma to uncover new insights into the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…2d). Furthermore, our analysis identifies OBI1-AS1 as a super-exclusive marker for astrocytes, corroborating previous findings reported by Mamivand et al 26 . The specific expression of OBIA-AS1 within astrocytes provides further evidence of its roles as a highly specific marker for this particular cell type (Fig.…”
Section: Identification Of Lncrna Markers and Lncrna-mrna Pairssupporting
confidence: 92%
“…2d). Furthermore, our analysis identifies OBI1-AS1 as a super-exclusive marker for astrocytes, corroborating previous findings reported by Mamivand et al 26 . The specific expression of OBIA-AS1 within astrocytes provides further evidence of its roles as a highly specific marker for this particular cell type (Fig.…”
Section: Identification Of Lncrna Markers and Lncrna-mrna Pairssupporting
confidence: 92%
“…Mamivand et al identified an epigenetically deregulated lncRNA OBI1-AS1 with decreased expression in glioblastoma multiforme. Hi-C and ChIP-Seq analysis showed that methylation of the CTCF binding site blocked the expression of OBI1-AS1 by influencing chromatin interactions [ 9 ]. LncRNAs also function as a scaffold for the recruitment of chromatin modifiers to target promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Several human genetic studies and animal studies also reported that genetic variations in the metabotropic glutamate receptor (mGluRs) subtype III may be associated with ADHD (47)(48)(49)(50)(51)(52)(53)(54). OBI1-AS1 expression has also been reported to be associated with astrocyte content, and some studies in recent years have attributed the pathophysiology of depression and mood disorders to astrocytes (45,(55)(56)(57). These can aid in the interpretation of our results to some extent, but our findings must be viewed with caution and be seen as preliminary.…”
Section: Discussionmentioning
confidence: 63%
“…Although the exact function of OBI1-AS1 remains unclear, several studies have suggested a regulatory role for the hybridization of natural antisense RNAs with endogenous mRNAs (43). Recent studies have reported that RNF219-AS1 was involved in the pathophysiology of ADHD (44), and that OBI1-AS1 has a potential role in glutamate receptor signaling and synaptic responses (45). Previous studies have linked genetic variations in the ion glutamate receptor to ADHD risk (46).…”
Section: Discussionmentioning
confidence: 99%